ANALYSIS OF CASH EXPENDITURE EFFECTIVENESS THROUGH THE ACCOUNTING INFORMATION SYSTEM OF PT. TELKOM INDONESIA REGIONAL DIVISION V - Mutiara Rachma Ardhiani; Yuni Sukandani; Siti Istikhoroh; Yurida Sasmita (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2020)
This study aims to analyze the procedures and effectiveness of cash expenditure through the accounting information system of PT. Telkom Indonesia Regional Division (Divre) V. This type of research is descriptive qualitative with the Miles and Hubermen model as a method of analysis. The results showed that the company had implemented computerized financial management through SAP (System Application and Product) and cash expenditure using the imprest fund system. The use of accounting information systems and procedures aims to protect assets and support the effectiveness of cash expenditure.